The tragedy (in) politics - Potestà, Andrea (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
Tragedy has historically been relegated outside the polis. Politics, it is usually said, is born in the ruins of the tragic world. However, the tragic force is constantly evoked in modernity as a transformative impulse of politics, whether in the form of a desire for catastrophe, of a revolution thought of as destruction and disaster of the rational order, or in the form of an annihilating suspension of the proper and free Cartesian subject. The problem of being-with has been constructed around the irruption of the tragic into the political. The present article interrogates this intersection, showing the ideological relapses, but also the transformative capacity of the political uses of the tragic.